Group portrait of the attendees of a Russian River Institute conference - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of the attendees of a Russian River Institute conference held in June and July 1933 in Russian River, California. Some of the group members can be seen holding signs and banners that read: "Theta Pi," "Port Stockton," "Octovians Eighth Avenue Oakland, " "Epworth," "First Berkeley," "Pep Banner," "Tau Sigma," "Hollister," "Manteca," "Dixon," "Tracy," and "Hooker Oak Cico."